A Gluten-Free Diet, Not an Appropriate Choice without a Medical Diagnosis. (1st July 2019) - Diez-Sampedro, Ana; Olenick, Maria; Maltseva, Tatayana; Flowers, Monica
Abstract : In the past, only people diagnosed with celiac disease, approximately 1% of the population, avoided gluten consumption through all their meals. However, popular media often now mistakenly present gluten-free foods as being a healthier choice, and more people have now concluded that gluten is a harmful part of the diet. A review of literature on gluten-free diets, gluten sensitivity, celiac disease, and attitudes toward gluten consumption was undertaken to examine the prevalence and consequences of adopting a gluten-free diet and to provide guidance to healthcare practitioners whose patients are now often adopting this diet without medical input. Aside from celiac disease, nonceliac gluten sensitivity (NCGS) occurs in those persons in which gluten ingestion leads to symptomatic manifestations in the absence of celiac disease or wheat allergy but who report a remission of certain symptoms after removing gluten from their diet. However, it was been shown that a large percentage of people who claim NCGS do not feel those manifestations under a double-blind challenge to gluten. Moreover, some parents, believing that ingesting gluten is detrimental for their health, adopt gluten-free diets for their children. A review of existing data shows that there are detrimental effects to going gluten free, including loss of the dietary fiber, deficiencies in dietary minerals and vitamins, and potential heavy metal exposure. Healthcare practitioners should query patients about their dietary choices, and in cases of questionable adoption of gluten-free diet, patients and parents are educated about the detriments of a gluten-free diet, and in cases where patients continue to insist on gluten-free foods, referrals to nutritional counseling are warranted in order to minimize potential harm.